Physician‐assisted Death: Ethical Implications for Emergency Physicians. (6th January 2019) - Derse, Arthur R.; Moskop, John C.; McGrath, Norine A.; Vearrier, Laura E.; Clayborne, Elizabeth P.; Goett, Rebecca R.; Limehouse, Walter E.
Abstract: Physician‐assisted death (PAD) has long been a strongly debated moral and public policy issue in the United States, and an increasing number of jurisdictions have legalized this practice under certain circumstances. In light of changing terminology, laws, public and professional attitudes, and the availability of published data about the practice, we review key concepts and terms in the ongoing PAD debate, moral arguments for and against PAD, the current legal status of PAD in the United States and in other nations, and data on the reported experience with PAD in those U.S. jurisdictions where it is a legal practice. We then identify situations in which emergency physicians (EPs) may encounter patients who request PAD or have attempted to end their lives with physician assistance and consider EP responses in those situations. Based on our analysis, we offer recommendations for emergency medical practice and professional association policy.